"But We Want to Work": The Movement of Child Workers in Peru and the Actions for Reducing Child Labor. Issue 3 (18th September 2017) - Maya Jariego, Isidro
Abstract: The program Edúcame Primero (Educate Me First) is an evidence‐based practice for eradicating child labor that has been applied with positive results in Colombia, Peru, and several Central American countries. In this article, we describe the difficulties of implementing the program in two poor areas of Lima (Peru) between 2014 and 2016. Specifically, we discuss three ethical challenges faced during the implementation of the program: (a) the existence of a movement of working children that defends the right of children to work; (b) the polarization of some community‐based associations and government institutions on how to deal with the problems of working children; and (c) the use of network indicators in the evaluation of the community's level of cohesion. Taking the Code of Ethics of the General Council of Associations of Psychologists in Spain as a guide, we adopted a consensus approach in planning and research design, combining different criteria of value with the participation of different stakeholders. The implementation of the program in Peru gave preference to developing skills in children over changing attitudes in relation to child protection, although the intervention openly declared its aims when engaging institutions and families. Finally, we address how social network research places special ethical demands on conventional ethical standards. Our experience with this project shows the importance of acting as a bridge between different stakeholders and assessing how all of them benefit from the intervention. Highlights: A movement of minors in Peru that defends the "right of children to work" is described. Social factors push children to work and negatively affect their quality of life. Listening to the voice of children must be made compatible with prevention of psychological damage. A consensus approach is proposed to involve diverse community organizations. Ethical challenges of a program for protecting the right of children to education are examined.